Prevalence, severity and characteristics of work-related musculoskeletal disorders amongst obstetrics and gynaecology professionals - Jadhav, Ashwini P.; Dharmapuri, Venu M.; Shyam, Ashok K.; Sancheti, Parag K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Backache is a common cause of morbidity among doctors and 50% of the obstetricians and gynaecologists suffering from this attribute it to working posture. Occupational injuries are poorly analyzed amongst these professionals. Work related injuries have adverse effect on health and work performance due to discomfort caused by pain. Awareness of ergonomics, correct posture and strategical assessment of risk factors is needed for the prevention of work related musculoskeletal injuries amongst obstetricians and gynaecologists. Methods: A survey based study was performed. Informed consent was taken for participation. The questionnaire included 16 questions categorised into: demographics; injury data; impact of injury; and general mental health. Hard copy of the questionnaire and online forms of the questionnaire were used to complete the data collection. Results: The response rate for the survey was 85% of the doctors who reported to have experienced pain in the last year. The most common site was back, which was followed by the neck and knees. 71.4% of doctors reported injuries attributed to work. Conclusions: The result demonstrates the prevalence of work related musculoskeletal injuries and their effects. These injuries are highly underreported. Ergonomics and work related injury prevention in this profession is a suggestion for solution as more data is needed regarding the analysis and risk factor assessment.